Security Tokens and Stablecoins Quick Start Guide: Learn How to Build STO and Stablecoin Decentralized Applications - Sun, Weimin; Wu, Xun (Brian); Kwok, Angela (Packt Publishing, Limited, 2019)
This essential guide will help any blockchain practitioner gain expertise in developing complete STO and stablecoins DApps. This book provides a quick introduction to basic ICO and STO concepts, and their differences. It will also help readers compile, test, and deploy their own contracts by altering the code provided in the book.